Lincoln's bishop : a president, a priest, and the fate of 300 Dakota Sioux warriors - Niebuhr, Gustav. (HarperOne, 2014)
"In the tradition of Doris Kearns Goodwin's Team of Rivals comes Gustav Niebuhr's compelling history of Abraham Lincoln's decision in 1862 to spare the lives of 265 condemned Sioux men, and the Episcopal bishop who was his moral compass, helping guide the president's conscience. More than a century ago, during the formative years of the American nation, Protestant churches carried powerful moral authority, giving voice to values such as mercy and compassion, while boldly standing against injustice and immorality. Gustav Niebuhr travels back to this defining period, to explore Abraham Lincoln's decision to spare the lives of 265 Sioux men sentenced to die by a military tribunal in Minnesota for warfare against white settlers--while allowing the hanging of 38 others, the largest single execution on American soil. Popular opinion favored death or expulsion. Only one state leader championed the cause of the Native Americans, Episcopal bishop, Henry Benjamin Whipple. Though he'd never met an Indian until he was 37 years old, Whipple befriended them before the massacre and understood their plight at the hands of corrupt government officials and businessmen. After their trial, he pleaded with Lincoln to extend mercy and implement true justice. Bringing to life this little known event and this extraordinary man, Niebuhr pays tribute to the once amazing moral force of mainline Protestant churches and the practitioners who guarded America's conscience. Lincoln's Bishop is illustrated with 16 pages of black-and-white photos"--